2019
DOI: 10.1177/1558689819872599
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Use of Mixed Methods–Grounded Theory: Developing Scales for a New Measurement Model

Abstract: Mixed methods–grounded theory (MM–GT) has emerged as a promising methodology that intersects the value of mixed methods with rigorous qualitative design. However, recent reviews have found that MM–GT empirical studies tend to lack procedural details. The purpose of this article is to apply the “best practices” for conducting MM–GT in a study designed to develop and then test a theoretical model for how undergraduate engineering students develop interest in the engineering PhD. This study contributes to the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…However, the linear regression (LR) analysis provides the conditional mean estimates, which display an incomplete picture of the dependent variable’s distribution because it cannot capture the coefficients of the independent variables for the entire regression (Mosteller and Tukey, 1977; Santos and Vieira, 2012). Previous studies have shown that the use of LR for heavy-tailed distributions and asymmetric variables is not advisable because it may lead to erroneous estimates (Howell Smith et al , 2020; Koenker and Bassett, 1978; Marrocu et al , 2015; Sánchez-Pérez et al , 2019; Wang et al , 2019). In light of these limitations, we checked whether the LR model assumptions were fulfilled.…”
Section: Methodsmentioning
confidence: 99%
“…However, the linear regression (LR) analysis provides the conditional mean estimates, which display an incomplete picture of the dependent variable’s distribution because it cannot capture the coefficients of the independent variables for the entire regression (Mosteller and Tukey, 1977; Santos and Vieira, 2012). Previous studies have shown that the use of LR for heavy-tailed distributions and asymmetric variables is not advisable because it may lead to erroneous estimates (Howell Smith et al , 2020; Koenker and Bassett, 1978; Marrocu et al , 2015; Sánchez-Pérez et al , 2019; Wang et al , 2019). In light of these limitations, we checked whether the LR model assumptions were fulfilled.…”
Section: Methodsmentioning
confidence: 99%
“…Recent developments in this field, such as using qualitative strategies for model specification therefore bypassing the need for exploratory confirmation analysis and increasing integration rigor by creating a dedicated methodology phase that thoroughly explains the transformation of qualitative findings into quantitative scale items (Howell Smith et al, 2020), are integral foundational knowledge for the current study. Moreover, the Transformativist Measurement Development Methodology builds on mixed methods strategies in scale development for attending to cultural sensitivity (Ungar & Liebenberg, 2011), use of a research phase structure of qualitative construct exploration, then integration scale development, and then quantitative scale validation (Enosh et al, 2015; Howell Smith et al, 2020), and use of mixed methods for rigorous construct validation . Last, mixed methods scholars have demonstrated how to use various frameworks for different approaches to scale development such as Rasch modeling (David et al, 2018), grounded theory (Howell Smith et al, 2020), and hierarchal linear modeling (Wong, 2015).…”
Section: Contribution To the Field Of Mixed Methodsmentioning
confidence: 99%
“…Moreover, the Transformativist Measurement Development Methodology builds on mixed methods strategies in scale development for attending to cultural sensitivity (Ungar & Liebenberg, 2011), use of a research phase structure of qualitative construct exploration, then integration scale development, and then quantitative scale validation (Enosh et al, 2015; Howell Smith et al, 2020), and use of mixed methods for rigorous construct validation . Last, mixed methods scholars have demonstrated how to use various frameworks for different approaches to scale development such as Rasch modeling (David et al, 2018), grounded theory (Howell Smith et al, 2020), and hierarchal linear modeling (Wong, 2015). The current study builds on this work by continuing the tradition of examining the benefits of different paradigms and approaches to scale development by exploring the use of a transformative lens in mixed methods scale development.…”
Section: Contribution To the Field Of Mixed Methodsmentioning
confidence: 99%
“…An arena of developing interest for mixed methods researchers concerns advancing procedures for intersecting (Plano Clark & Ivankova, 2016) or scaffolding together (Fetters, 2020) two methodologies in a program of research for integration in the methodological dimension (Fetters & Molina-Azorin, 2017; Greene, 2015). Relevant examples include mixed methods grounded theory (Creamer, 2018; Guetterman et al, 2019; Howell Smith et al, 2020; Johnson et al, 2010; Walsh, 2015) and mixed methods case study (Guetterman & Fetters, 2018; Plano Clark & Ivankova, 2016). A gap in the literature has been the intersection of longitudinal mixed methods with a mixed methods case study.…”
mentioning
confidence: 99%